Face Recognition and Description Abilities in People with Mild Intellectual Disabilities. Issue 5 (8th August 2013) - Gawrylowicz, Julie; Gabbert, Fiona; Carson, Derek; Lindsay, William R.; Hancock, Peter J. B.
<x xml:space="preserve">Abstract</x> Background People with intellectual disabilities (ID) are as likely as the general population to find themselves in the situation of having to identify and/or describe a perpetrator's face to the police. However, limited verbal and memory abilities in people with ID might prevent them to engage in standard police procedures. Method Two experiments examined face recognition and description abilities in people with mild intellectual disabilities (mID) and compared their performance with that of people without ID. Experiment 1 used three old/new face recognition tasks. Experiment 2 consisted of two face description tasks, during which participants had to verbally describe faces from memory and with the target in view. Results Participants with mID performed significantly poorer on both recognition and recall tasks than control participants. However, their group performance was better than chance and they showed variability in performance depending on the measures introduced. Conclusions The practical implications of these findings in forensic settings are discussed.